Do shorter inter‐stimulus intervals in the go/no‐go task enable better assessment of response inhibition? - Hasegawa, Akira (Scand J Psychol, 2020)
Young, Sutherland, and McCoy indicated that a Go/No‐Go Task (GNG) becomes more difficult as the inter‐stimulus intervals (ISIs) becomes shorter. However, is the number of commission errors under extremely short ISIs a useful metric for assessing response inhibition? This study challenges the assumption that a shorter ISI in the GNG enables better assessment of response inhibition. University students (N = 213) completed the GNG, the Conners Continuous Performance Test 3rd Edition (CCPT), and the Modified Stroop Task. The GNG comprised four blocks of 400, 600, 800, and 1000 ms ISIs, whereas the stimulus presentation was fixed at 250 ms. Consistent with Young et al., shorter ISIs in the GNG resulted in more commission errors. In the block with the shortest ISI, participants also failed more frequently in responses in go trials than in the other blocks, which appears to increase in error variance of commission errors. Consistent with this interpretation, the association between the number of commission errors in the block with 400 ms ISI and CCPT performance was weaker than those between the number of commission errors in other blocks and CCPT performance. It is concluded that using the number of commission errors in the condition with extremely short ISIs in the GNG might be inappropriate for assessing response inhibition.